Study on water quality simulation and dynamic water environment capacity of Helan County section of the third drainage ditch in Ningxia - Yang, Cheng; Zheng, Lanxiang; Zhang, Zunyang; Feng, Minquan (Frontiers in Ecology and Evolution, 2022)
The water environmental capacity of the Helan County section of the third drainage ditch in Ningxia was analyzed. The Daily discharge and water level are calculated according to the measured data. The daily concentration of each water quality index in the study area was simulated by one-dimensional hydrodynamic water quality mathematical model. The monthly water environmental capacity was calculated by using dynamic water environmental capacity model. The results show that the simulated water quality values at the outlet section of the study area are consistent with the measured values, and the one-dimensional hydrodynamic water quality model is reliable. In the study area, the discharge of water quality indexes exceeded the standard most seriously in August, and the surplus of water environmental capacity is the most in September, BOD5 and TN exceeded the standard most seriously, and the water environmental capacity of COD, PV and NH3-N was large.